Reconfiguring Islamic Journalism in the AI Era: Ethics and Algorithmic Disruption in Digital Da’wah - M Yoserizal Saragih (International Forum of Researchers and Lecturers, 2025)
This study investigates how artificial intelligence (AI) is transforming Islamic journalism and digital da’wah by analyzing the ethical challenges posed by algorithmically mediated media. Employing a critical-interpretive approach, the research examines how algorithmic logic impacts the production, visibility, and ethical dimensions of Islamic content on platforms such as YouTube and TikTok. The findings reveal a growing tension between Islamic communication principles—sidq (truth), amanah (trust), and hikmah (wisdom)—and the operational values of AI systems that prioritize virality, personalization, and engagement metrics. This paper contributes to global discourse by proposing a hybrid ethical framework that bridges Islamic communication ethics with digital media accountability. It argues for an integrative model where spiritual integrity, transparency, and justice guide the development and use of AI in Islamic media contexts.